TINJAUAN SIYASAH SYAR’IYAH TERHADAP PENETAPAN BATAS USIA NIKAH (Studi Kritis Terhadap Penetapan Usia Nikah Di Indonesia) - Muhammad Nurul Fahmi (Al-Majaalis : Jurnal Dirasat Islamiyah, 2020)
Various countries including Indonesia have enacted laws regulating the age limit for marriage. The determination of thelimit is certainly not free from criticism and controversy. On the other hand, the presence of a state to regulate people's affairs is highly emphasized in Islam, both relating to religious issues and world problems.This is what is known as siyasah shar'iyah ‘good governance in Islam’. However, the determination of the age limit for marriage needs to be studied further from the perspective of siyasah shar'iyah. This study aims to determine the general concept of siyasah shar'iyah, the stipulation of the age of marriage in Islam, the age limit for marriage in Indonesia, and the conformity of these rules to the concept of siyasah shar'iyah.This research is a library research that uses a qualitative approach. The results of this study indicate that the general concept of siyasah shar'iyah is the authority of the leader to regulate matters that have not been determined by sharia arguments, as well as things in sharia that are not permanent or have many legal points of view. As for the age limit for marriage, it is not specified in Islam. However, a guardian (father) may even marry off their young children. Meanwhile in Indonesia, a person is not allowed to get married before reaching the age of 19, whether male or female. This stipulation of the age limit for marriage is not in line with the concept of siyasah shar'iyah. As this has legal consequences that are contrary to what has been established by Islam through the sharia argument, which is that it is permissible for someone to marry under that age.On the other hand, it also contradicts the recommendation of the Sharia to hasten marriage if it is possible.